An ecosystem risk assessment of temperate and tropical forests of the Americas with an outlook on future conservation strategies. Issue 2 (15th January 2019) - Ferrer‐Paris, José Rafael; Zager, Irene; Keith, David A.; Oliveira‐Miranda, María A.; Rodríguez, Jon Paul; Josse, Carmen; González‐Gil, Mario; Miller, Rebecca M.; Zambrana‐Torrelio, Carlos; Barrow, Edmund
Abstract: Forests of the Americas and the Caribbean are undergoing rapid change as human populations increase and land use intensifies. We applied the IUCN Red List of Ecosystems (RLE) criteria and simple cost‐efficiency analyses to provide the first regional perspective on patterns of relative risk integrated across multiple threats. Based on six indicators of ecosystem distribution and function, we find that 80% of the forest types and 85% of the current forest area is potentially threatened based on RLE criteria. Twelve forest types are Critically Endangered due to past or projected future deforestation, and Tropical Dry Forests and Woodland have highest threat scores. To efficiently reduce risks to forest ecosystems at national levels, scenario analyses show that countries would need to combine large forest protection measures with focused actions, tailored to their sociopolitical context, to help restore ecological functions in a selection of threatened forest types.